1979
DOI: 10.2527/jas1979.4851049x
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Gains and Carcass Characteristics of Swine of Two Degrees of Fatness Slaughtered at Three Weights

Abstract: SummaryTwo hundred barrows and gilts were slaughtered at 100, 113 and 127 kg live weight. The sample was comprised of 36 litters, of which six litters within each breed of sire (Duroc, Hampshire and Yorkshire) were classified as fat litters (2.36 cm) and six litters classified as lean litters (2.16 cm) on the basis of litter mean backfat probes taken at 68 kg live weight.Growth traits were evaluated from 9 weeks of age until the designated slaughter weight. Carcasses from the first replication (18 litters) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 7 publications
4
6
0
Order By: Relevance
“…Our results suggest that overall growth rates and feed efficiencies are largely unaffected by slaughter weights between 100 and 160 kg ( Table 2). The lack of a slaughter weight effect on growth rate agrees with the results of Neely et al (1979), who found no significant difference in daily gain in pigs from 68 kg to 100, 113, or 127 kg. Kanis et al (1990) reported that barrows and gilts grew substantially more slowly between 60 kg and 140 kg that between 60 and 100 kg.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Our results suggest that overall growth rates and feed efficiencies are largely unaffected by slaughter weights between 100 and 160 kg ( Table 2). The lack of a slaughter weight effect on growth rate agrees with the results of Neely et al (1979), who found no significant difference in daily gain in pigs from 68 kg to 100, 113, or 127 kg. Kanis et al (1990) reported that barrows and gilts grew substantially more slowly between 60 kg and 140 kg that between 60 and 100 kg.…”
Section: Resultssupporting
confidence: 90%
“…However, when expressed as a percentage of side weight, these changes were equivalent to decreases of .65 and .32 percentage units, respectively. Carr et al (1978) and Neely et al (1979) also reported a small decrease in percentage trimmed, boneless yields in pigs slaughtered between 45 and 136 kg and 100 and 127 kg, respectively. Other workers have shown little change in percentage lean cut yield with slaughter weight (Fortin, 1980;Martin et al, 1981).…”
Section: Resultsmentioning
confidence: 91%
“…Barrows had higher average daily gains ( P < .05) and lower gain:feed ratios ( P < .001) than gilts, which is consistent with the literature (Aalhus et al, 1991;Sather et al, 1991c). There was no association between slaughter weight and growth rates, but as slaughter weight increased there was a reduction ( P < .05) in gain:feed, which again is consistent with the literature (Neely et al, 1979;Cisneros et al, 1996).…”
Section: Resultssupporting
confidence: 88%
“…However, published results on the effect of SW on this variable are inconsistent. Martin et al (1980) and Corino et al (2008) have reported that the primal yield percentage decreased with increasing SW, whereas in Neely et al (1979) and Park et al (2007), SW exerted no influence on this variable.…”
Section: Primal Yieldmentioning
confidence: 97%
“…The ADG barely changes with increasing SW between 110 and 135±5 kg in lean-genotype finishing pigs (Neely et al, 1979;Lee et al, 2006;Park et al, 2007Park et al, , 2009b, although in a study of Latorre et al (2008), ADG did not change up to 125 kg and declined thereafter. Furthermore, Cisneros et al (1996) have reported that ADG of finishing pigs beginning from 60 kg had no relation to final BW between 100 and 160 kg.…”
Section: Growth Efficiencymentioning
confidence: 99%